2019
DOI: 10.1002/jsde.12246
|View full text |Cite
|
Sign up to set email alerts
|

Sophorolipid Biosurfactants Activate Taste Receptor Type 1 Member 3‐Mediated Taste Responses and Block Responses to Bitter Taste In Vitro and In Vivo

Abstract: Sophorolipids (SL) are typically produced and secreted by select nonpathogenic yeast species (i.e., Candida) from renewable substrates. They are currently being used by industry on a limited basis in formulations for cleaning solutions as well as laundry and dishwashing detergents. Due to the nature of their chemical structure, it was hypothesized that SL would demonstrate taste‐sensory properties. In this study, SL were produced via fermentation on a mixed substrate platform with glucose and either palmitic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…Candida albicans SC5314 and Candida glabrata CBS138 sophorolipids have been reported to have emulsifying activities in olive oil, soy oil, almond oils and mustard by 40–50% [ 75 ]. In addition, SLs have sensory properties on the palate and responses induced in human taste buds cell cultures, enabling their application to modulate the taste of food and drugs [ 76 ].…”
Section: Structural Classes Properties and Applicationsmentioning
confidence: 99%
“…Candida albicans SC5314 and Candida glabrata CBS138 sophorolipids have been reported to have emulsifying activities in olive oil, soy oil, almond oils and mustard by 40–50% [ 75 ]. In addition, SLs have sensory properties on the palate and responses induced in human taste buds cell cultures, enabling their application to modulate the taste of food and drugs [ 76 ].…”
Section: Structural Classes Properties and Applicationsmentioning
confidence: 99%
“…The structure of sophorolipids is comprised of a sophorose sugar molecule united to a hydroxylated long‐chain fatty acid 62 . MELs are characterized by mannose sugar linked to a fatty acid and are subdivided according to the length of the hydrophobic chain (fatty acid) and degree of saturation and/or acetylation in the C4 and C6 positions of the monosaccharide.…”
Section: Biosurfactantsmentioning
confidence: 99%
“…A recently published study using in vitro and animal models of taste response identified sophorolipids (SL) as a new candidate bitter reducer (Ozdener et al, 2019). SL are biosurfactant molecules produced from renewable substrates by some nonpathogenic yeast species, including Candida bombicola (Ashby et al, 2008, 2013; Develter and Lauryssen, 2010; Rawat et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Preapplication of SL to cultured human taste papillae cells reduced subsequent responses to a mixture of bitter compounds (Ozdener et al, 2019). Further, preapplication of SL to the tongues of anesthetized mice reduced subsequent bitter responses of the chorda tympani nerve, a branch of cranial nerve VII that carries signals from taste buds in the anterior tongue to the brain (Ozdener et al, 2019). Both results suggest that SL may reduce bitterness.…”
Section: Introductionmentioning
confidence: 99%